In silico (Eco)toxicology and molecular docking of halogenated and oxygenated rotenoid derivatives - Damião Sampaio de Sousa; Anthony Barbosa Belarmino; Victor Moreira de Oliveira; Francisco Rogênio da Silva Mendes; Emmanuel Silva Marinho; Gabrielle Silva Marinho (The Journal of Engineering and Exact Sciences)
The rotenoids are compounds widely disseminated in the agro-industrial and chemical-pharmacological sectors due to their structural constitution and versatility in biological activities, however, these present toxic activity for fish. Thus, the objective of this study is an in silico (eco)toxicological investigation of synthetic halogenated and oxygenated rotenoids with the use of aquatic bioindicators and molecular docking aiming to understand the biochemical behavior and environmental dynamics of these compounds. Therefore, it is inferred that the synthetic rotenoids denoted toxicological response at the chronic level made possible through physicochemical data and correlations between environmental dynamics, notwithstanding, the molecular coupling data corroborated with ecotoxicological assay enabling the rotenoids present bio-concentrative tendencies along the trophic chain causing deleterious effects in more developed organisms. Thus, the study is at an initial level, which enables new approaches in vitro and in vivo models for improvement and development of this study.